The Molecular Determinants of Erythrocyte Removal Impact the Development of Metabolic Dysfunction-Associated Steatohepatitis - Papadopoulos, Charalampos (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
Metabolic dysfunction-associated steatohepatitis (MASH) is a major cause of a worldwide clinical and financial burden. Despite the tremendous efforts for untangling the molecular mechanisms, there is still a need for defining specific therapeutic targets. In this study, the author will focus on the role of erythrocyte death and hepatic erythrophagocytosis in MASH. Evidence indicates that erythrolysis prior to erythrophagocytosis protects against the development of MASH, while phagocytosis of intact erythrocytes culminates in hepatic inflammation. Furthermore, understanding the balance between erythrolysis and intact erythrocyte engulfment could lead to the development of new strategies for the treatment of MASH.
Keywords: efferocytosis